(untitled) (REMUNOM, 2026)
This article analyzes the phenomenon of digital energy colonialism as a contemporary expression of the coloniality of power within the context of the global energy transition. It argues that, under the discourse of sustainability, technological innovation, and decarbonization, historical dynamics of exploitation, territorial dispossession, and economic subordination are reproduced, now mediated by digital infrastructures, technological platforms, and regimes of algorithmic governance. The study draws on decolonial theory and critical perspectives on energy colonialism and green colonialism to demonstrate how the Global South continues to be positioned as a supplier of strategic natural resources, sacrifice territories, and material bases for the expansion of “green” and digital technologies, while economic, informational, and decision-making benefits remain concentrated in the Global North and among transnational elites. It is argued that the digitalization of the energy transition intensifies neo-extractivism by incorporating data extraction, technological control, and the financialization of nature as new vectors of domination. The article concludes that digital energy colonialism deepens socio-environmental inequalities, undermines the self-determination of peoples and traditional communities, and challenges hegemonic paradigms of climate justice, calling for the construction of energy and technological alternatives grounded in socio-environmental justice, territorial sovereignty, and epistemological plurality.